IBM WebSphere Portal 8 : Web Experience Factory and the Cloud : build a comprehensive web portal for your company with a complete coverage of all the project lifecycle stages /: Web Experience Factory and the Cloud : build a comprehensive web portal for your company with a complete coverage of all the project lifecycle stages. (2012) - Camargo, Chelis; Martens, Helmar
No abstract available